Arterial oxygenation and acid–base status before and during oxygen supplementation in captive European bison (Bison bonasus) immobilized with etorphine-acepromazine-xylazine - Gardoni, Nino; Björck, Sven; Morelli, Jacopo; Evans, Alina L.; Barros, Daniela S. B.; Wiklund, Rikard; Græsli, Anne Randi; Thiel, Alexandra; Arnemo, Jon M.; Lian, Marianne (Frontiers in Veterinary Science, 2023)
Chemical immobilization of captive European bison (Bison bonasus) is often required for veterinary care, transportation, or husbandry practices playing an important role in conservation breeding and reintroduction of the species. In our study, we evaluated the efficiency and physiological effects of an etorphine-acepromazine-xylazine combination with supplemental oxygen in 39 captive European bison. Animals were darted with a combination of 1.4 mg of etorphine, 4.5 mg of acepromazine and 20 mg of xylazine per 100 kg based on estimated body mass. Arterial blood was sampled on average 20 minutes after recumbency and again 19 minutes later and analyzed immediately with a portable i-STAT analyzer. Simultaneously, heart rate, respiratory rate and rectal temperature were recorded. Intranasal oxygen was started after the first sampling at a flow rate of 10 mL.kg-1.min-1 of estimated body mass until the end of the procedure. The initial mean partial pressure of oxygen (PaO2) was 49.7 mmHg with 32 out of 35 sampled bison presenting with hypoxemia. We observed lowered values of respiratory rate, decreased pH and mild hypercapnia consistent with a mild respiratory acidosis. After oxygen supplementation hypoxemia was resolved in 21 out of 31 bison, but respiratory acidosis was accentuated. Bison immobilized with a lower initial drug dose required supplementary injections during the procedure. We observed that lower mean rectal temperatures during the immobilization event were significantly associated with longer recovery times. For three bison regurgitation was noticed with presence of ruminal fluid in the mouth and nostrils. No mortality or morbidity related to the immobilizations were reported for at least two months following the procedure. Based on our findings, we recommend a dose of 0.015 mg.kg-1 etorphine, 0.049 mg.kg-1 acepromazine and 0.22 mg.kg-1 xylazine. This allows to reduce the need for reinjection and obtain a sufficient level of immobilization, with only one dart, for management and husbandry procedures in captive European bison. Nevertheless, this drug combination is associated with development of marked hypoxemia, mild respiratory acidosis, and a small risk of regurgitation. Oxygen supplementation is recommended when using this protocol.